Hubungan Tonsilektomi Dengan Kualitas Hidup Pada Anak Di Rumah Sakit Detasemen Kesehatan Tentara Bandar Lampung Tahun 2018 - Abimanyu Darmawan; Mukhlis Imanto (Medula, 2022)
Chronic tonsillitis is an inflammatory disease of the tonsils that often occurs in children. The action taken in chronic tonsillitis is tonsillectomy. Given the tonsils as a body defense system is still a matter of controversy among experts. Chronic tonsillitis that has been done with tonsillectomy will affect the quality of life. Quality of  life consists of emotions, social, school, and physical. The aim of this study is to determine the relationship of tonsillectomy with quality of life in children. The design used in this study was observational analytic with a case control approach. Data collected by analyzing medical records and distributing questionnaires to 44 children aged 5-12 years. Sampling methods done by purposive sampling. The research instrument used was Pediatric Quality of Life Inventory (PedsQL). Data were analyzed with chi square. Most of tonsillectomy patients have good quality of life with a percentage of 77,3% compared to those without tonsillectomy with a percentage of 31,8%. Tonsillectomy was statistically related with quality of life in children at the Hospital Detasemen Kesehatan Tentara Bandar Lampung with p value = 0,006 (p<0,05). Based on this study, we can conclude that there was a relationship between tonsillectomy and quality of life in children at the Hospital Detasemen Kesehatan Tentara  Bandar lampung in 2018. Chronic tonsillitis is an inflammatory disease of the tonsils that often occurs in children. The action taken in chronic tonsillitis is tonsillectomy. Given the tonsils as a body defense system is still a matter of controversy among experts. Chronic tonsillitis that has been done with tonsillectomy will affect the quality of life. Quality of  life consists of emotions, social, school, and physical. The aim of this study is to determine the relationship of tonsillectomy with quality of life in children. The design used in this study was observational analytic with a case control approach. Data collected by analyzing medical records and distributing questionnaires to 44 children aged 5-12 years. Sampling methods done by purposive sampling. The research instrument used was Pediatric Quality of Life Inventory (PedsQL). Data were analyzed with chi square. Most of tonsillectomy patients have good quality of life with a percentage of 77,3% compared to those without tonsillectomy with a percentage of 31,8%. Tonsillectomy was statistically related with quality of life in children at the Hospital Detasemen Kesehatan Tentara Bandar Lampung with p value = 0,006 (p<0,05). Based on this study, we can conclude that there was a relationship between tonsillectomy and quality of life in children at the Hospital Detasemen Kesehatan Tentara  Bandar lampung in 2018.